2005
DOI: 10.1634/theoncologist.10-6-392
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Epirubicin and Thalidomide in Unresectable or Metastatic Hepatocellular Carcinoma

Abstract: Background. The median survival time for patients with unresectable hepatocellular carcinoma (HCC) is <6 months, and no effective standard systemic chemotherapy is available. Both epirubicin (Ellence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…Advanced hepatocellular carcinoma (HCC) carries a poor prognosis, and systemic therapy with cytotoxic agents shows no survival benefit (1). The orally available, multitargeting receptor tyrosine kinase inhibitor sorafenib is the first agent showing significant improvement in median overall survival in 2 randomized phase III trials in advanced HCCs (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Advanced hepatocellular carcinoma (HCC) carries a poor prognosis, and systemic therapy with cytotoxic agents shows no survival benefit (1). The orally available, multitargeting receptor tyrosine kinase inhibitor sorafenib is the first agent showing significant improvement in median overall survival in 2 randomized phase III trials in advanced HCCs (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Thomas et al [30] showed that in patients with advanced HCC the combination of bevacizumab and erlotinib exerted significant, clinically meaningful anti-tumour activity. Zhu et al [31] documented that sunitinib exhibited modest anti-tumour activity in advanced HCC. We developed GMS, whose size and dissolution time can be manipulated, as an embolic agent [18].…”
Section: Anti-tumour Effects Of Co-treatment Of Tae With Thalidomidementioning
confidence: 99%
“…It was used in treating advanced HCC patients, mainly due to its anti-angiogenic property. However, single-agent thalidomide [37,38] and its combinations with epirubicin or interferon [39,40] only produced a response rate of 3.1%-6.3% with a median survival of 2.7-6.8 mo. In view of its limited activity and frequent association with treatment-related toxicities, it is now seldom included in the treatment algorithm for advanced HCC patients.…”
Section: Thalidomidementioning
confidence: 99%